Media representations of social conflicts: Identifying theoretical foundations for typology - Elena Vartanova; Anna Gladkova; Denis Dunas (World of Media, 2023)
The paper suggests integrated theoretical foundations for systemizing media representations of social conflicts and defining major roles attributed to media coverage of conflicts in current academic research. Using theoretical modeling, we identify the main types of social conflicts identified by Russian and foreign scholars, which is essential for revealing diverse media representations of conflicts. Then we show the key variables used by Russian and foreign media scholars to categorize the roles played by media in representation of conflicts, and discuss the results within broader media conflictology paradigm.